Descrição do conceito de deficiência a partir da mídia cinematográfica: uma análise comportamental - Cabral, Cibele Zanirato [UNESP]; Lotti, Beatriz [UNESP]; Cestari, Karla [UNESP]; Almeida-Verdu, Ana C. M. [UNESP]; Carrara, Kester [UNESP] (My University, 2010)
This work pointed out forming elements from the conception of special necessities that the media show the audience by the movies. An expression description has established special needs and they were identified as keywords on a search of movies (1994-2004) which were analyzed by two observers, according to a script. The results showed that 33 of the movies selected, 39.9% were classified in the ramacategory; 64% shows the disability as organic nature and 57% with predominant clinic diagnoses. Many labeled practices were identified (85%) and few accessibilities options (76%). In 85% of the movies the disability is said a manifestation of problems with few (58%) professionals intervention. The results are discussed by the media role on the concept formation of disabilities, offering interaction models with important role on social practice specification or unsuitable to the relation with the diversity and to the culture.
Description by media cinematographic of the disability concept: A behavioral analysis
Keywords: Behavior Analysis; Cultural practices; Deficiency; Media; Special needs